Hematological, Biochemical, and Nutritional Status in Young Male Basketball Players - Tok, Ozlem; Bayramoglu, Alp; Arent, Shawn M. (LIPPINCOTT WILLIAMS \& WILKINS, 2016)
Annual Meeting of the American-College-of-Sports-Medicine (ACSM), Boston, MA, MAY 31-JUN 04, 2016